Discrepancy Between Dental Age Estimation and Stated Age in Child Marriage Dispensation Requests: A Multivariate Forensic Odontology Study in Indonesian Religious Courts - Syaifudin Syaifudin; Iting Shofwati; Eduardo Michael Perez; Muhammad Faiz (Phlox Institute: Indonesian Medical Research Organization, 2026)
Introduction: Age misrepresentation in child marriage dispensation petitions represents a critical yet underexamined medicolegal challenge in Indonesia, where civil registration deficits disproportionately affect rural communities and create conditions in which biological age and administrative age may diverge substantially. Methods: This retrospective cross-sectional study evaluated the magnitude and determinants of age discrepancy between forensic dental age estimation and stated civil age among 148 petitioners referred for odontological evaluation at Religious Courts in Province X between January 2020 and December 2023. Dental age was estimated from panoramic radiographs using the Demirjian seven-tooth staging method for the mandibular dentition, supplemented by the modified Kötteles classification for third molar root development. Results: Inter-rater agreement between two calibrated forensic odontologists was excellent (ICC=0.91, 95% CI 0.87–0.94). Age overstatement — defined as the stated age exceeding the estimated dental age by more than one year — was identified in 52 cases (35.1%), while concordance was observed in 96 cases (64.9%); no case of understatement was recorded. On multivariate binary logistic regression adjusting for sex, petition reason, and stated age, rural residence (OR=2.14, 95% CI 1.06–4.33, p=0.035) and a court-granted dispensation decision (OR=2.60, 95% CI 1.31–5.16, p=0.008) were independently associated with age overstatement. Conclusion: Forensic odontological evaluation identified clinically significant age discrepancies in over one-third of cases, underscoring the inadequacy of civil documentation as the sole arbiter of age eligibility in marriage dispensation proceedings. Systematic integration of standardised dental age estimation into the judicial framework for dispensation adjudication in Indonesia is recommended.